A volta da realidade das margens - Paulo Roberto Tonani do Patrocínio (Estudos de Literatura Brasileira Contemporânea)
This article discusses the persistence of forms of representation of the urban periphery that are based on realism. It is with this approach that I propose to comment on some of the contemporary literary production, especially prose that describes marginalizing situations in Brazil’s big cities. The path explored is anchored in the reading of contemporary texts that highlight aspects that establish the return of a literary project that has the search for a review of Brazilian reality within fiction as its main axis.